KOMUNIKASI PENYULUHAN DINAS PEMADAM KEBAKARAN DALAM PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN PADA TAMAN KANAK-KANAK DI PEKANBARU - Irene Margareta Sabrina; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Fires are a dangerous threat and can cause loss of life if we do not make appropriate efforts to prevent fires. In Pekanbaru fire events always occur every year. Ranging from building fires to land fires. Therefore, the Pekanbaru City Fire Service conducted counseling on fire prevention to early childhood. This extension aims to provide knowledge about fire prevention and control. Counseling on fire prevention is important to do so later what is taught to them can be applied when they are adults if they experience a fire accident. The purpose of this counseling is to determine the selection of communicators on counseling, counseling messages, counseling media, counseling targets and the effects of counseling.The research method used in this study is a qualitative research method. Using purposive technique by interviewing 15 informants consisting of Secretaries, Employees and Staff Capacity Building for the Pekanbaru Fire Department, Teachers, Parents and Kindergarten students. Data collection techniques with interviews, observation, and documentation. Data analysis techniques use the Miles and Huberman models. To achieve data validity, researchers used extended participation and triangulation.The results of this study are communicators on counseling chosen based on the knowledge and experience they have, who become communicators at counseling are extension and training staff who already have extension certificates. The message conveyed at the counseling was informative and persuasive by giving material about fires and inviting participants not to play fire. Media used by the Fire Department in counseling on kindergartens in the form of infocus, microphones and speakers. In conveying the message the communicator also uses supporting tools such as APAR gas cylinders, fire-resistant suits, safety helmets so that children can see the shape of the images delivered in the OHP. The target of this education is kindergarten children. The effect of this counseling is that kindergarten children no longer want to play fire, know how to prevent and overcome fires, remind people around to always be on fire.